Groups whose lattices of normal subgroups are factorial - Rajhi, A. (Algebra and Discrete Mathematics, 2020)
We prove that the groups G for which the lattice of normal subgroups N(G) is factorial are exactly the UND-groups, that is the groups for which every normal subgroup have a unique normal complement, with finite length.